Intensifying focus on service quality in higher education institutions: emotional and spiritual intelligence - Saad, Mazni; Ahmad Shah, Norliana; Supian, Kamisah; Abdul Rani, Anita (e-International Publishing House, Ltd., UK, 2020)
The influence of Emotional and Spiritual Intelligence was investigated on the lecturers’ Service Quality. Based on stratified sampling method, the results confirmed that both types of intelligence have a positive and significant influence on the lecturers’ teaching progression. In conclusion, if the average level of each intelligence was good, then the level of Service Quality would also excel accordingly. The study highlights the need to have both EQ and SQ as it will encourage and motivate them into giving their best service to the university as well as their highest commitment towards giving students the best quality learning experience.